DIGITAL TRAINING OF KINEMASTER APPLICATION FOR LEARNING VIDEO: PERSPECTIVES FROM KINDERGARTEN SCHOOL TEACHERS - Umniyyatul Makmuroh (International Journal of Research in Education, 2021)
This study aims at finding out the kindergarten teachers’ perspectives after joining digital training of Kinesmaster application to create video of learning. This study focused on the perspectives on the digital training and the application itself. By working on description in explaining the data, this study applied descriptive qualitative design. 20 teachers of kindergarten participated in this study by selecting them randomly. To gain the data, open-ended questionnaire was given to the participants and semi-structured interview was conducted to gain deeper data. The data were analyzed by sorting the responses of each questions and then confirmed to the transcribed interview data. Based on the analysis result, it was revealed that digital training was responded positively. Most of the teachers felt good during the training. This training was also assumed to be able to improve their teaching performance and creativity. The use of Kinemaster application in the training also got good feedback. It is considered as a good, complete, and easy to use. Therefore, this training is expected to be able to make teachers meet their teaching goals.